Pendampingan Penerapan Program Penguatan Pendidikan Karakter di SMP Negeri 4 Pandak Kabupaten Bantul - Rinawati Zailani; Choirun Nisaa’; Devi Merina Tuz Sa’diyah; Roberta Aris Sucahyaningsih (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The implementation of character education in schools must be based on basic character values, which are developed into more or higher values ​​(neither absolute nor relative) according to the needs, conditions and environment of the school itself. Assistance in implementing the character education strengthening program is carried out to form students who are embedded in religious values, have nationalist values, have an independent and cooperative attitude. The programs carried out include carrying out faith building activities, mental and physical development, and environmental love activities. Supporting factors in the character education strengthening program at SMP Negeri 4 Pandak are the intervention of the academic community, both teachers and principals as good role models, as well as support from the students' parents. Apart from that, this program also has several obstacles such as limited facilities and infrastructure and not optimal habituation activities carried out.